Smart Irrigation System Using Raspberry Pi - Sahrom, Ahmad Syamil; Aminuddin, Raihah (2020)
Commonly known as IoT, Internet of Things is a demanding area in technology that is growing daily. Millions of devices have been created to make humans life easier. IoT has been largely contribute to home automation where every devices and home appliances can be connected to Internet and interact with each other. Suitable for people who are working but currently leaving plants at home with nobody to take of it. Thus, by applying the IoT concept, this paper provides design and implementation of Smart Irrigation System using Raspberry Pi as their main component. Raspberry Pi, which is a palm-size computer is capable of running a machine learning process within it. The irrigation is automated by using machine learning algorithm that has been implemented on the system. This system uses moisture sensor, humidity and temperature sensor, and ultrasonic sensor. The collected sensors data then is transferred through Firebase database, an online database that used to connect with android application. The sensors data can be viewed by the user through android application in real time. This project can go beyond further from what has been implemented by applying this project into a large scale of crops instead of using it at home only.